The Effect of Concentration and Timing of Application of Green Tonik Foliar Fertilizer on theGrowth and Yield of Cucumber (Cucumis sativusL.) Mercy Variety - Hakim, Rahman (Universitas 17 Agustus 1945 Samarinda, 2018)
This experiment aims to: (1) to study of the effect of concentration and application timing of Green Tonik foliar fertilizeras well as their interaction on the growth and yield of cucumber plants; and (2) to find proper concentration and application timing of Green Tonik foliar fertilizer for better growth and yield of cucumber plants.The experiment carried out from March 2016 to May 2016, in the Village of Muara Bengkal Ilir, Muara Bengkal Subdistrict, East Kutai District. It applied Completely Randomized Block Design with factorial experiment 4 x 3 and three replications. The first factor was the concentration of the Green Tonik foliarfertilizer (K) consists of 4 levels, namely: no Green Tonik foliar fertilizer application (k0), 1 ml l-1 water(k1), 2 ml l-1 water(k2), and 3 ml l-1 water(k3). The second factor wasinterval of the application time of Green Tonik foliar fertilizer(W) consists of 3 levels: 5, 10, 15, 20, and 25 days after planting (w1), 7, 14, 21, 28, and 35 days after planting (w2), and 10, 20, 30, 40, and 50 days after planting (w3).Result of the experiment revealed that : (1) concentration of Green Tonik foliar fertilizer application was affected significantly to very significantly on plant lenght at 30 and 45 days after planting, days of plant flowered, number of fruits per plant, diameter of fruit, weight of one fruit, and production of fruits, but no significant on the plant lenght at 15 days after planting, and lenght of fruit. The highest production of fruit is attained by the 2 ml l-1 water (k3), namely 54,67 Mg ha-1, In reverse, the least production is attained by without Green Tonik foliar fertilizer (k0), namely 24,00 Mg ha ̵ ¹; (2) interval of Green Tonik foliar fertilizer application time was no significant on the plant lenght at 15 and 45 days after planting, days of plant flowered, number of fruits per plant, lenght of fruit, diameter of fruit, weight of one fruit, and production of fruit, but affected significant on the plant lenght at 30 days after planting; and (3) interaction between concentration and application timing of Green Tonik foliar fertilizer was no significant on the all parameters observed.